Hematologic parameters in thrombocytopenic patients with dengue fever (Journal of Pathology of Nepal, 2022)
Background: Dengue fever is an endemic disease in Nepal that has shown increasing incidence each passing year. Dengue has a wide range of clinical presentations and laboratory findings. Thrombocytopenia is a common finding in dengue-infected patients along with other findings like leukopenia, lymphocytosis, raised hematocrit, and elevated liver enzymes. Thrombocytopenia is an indicator of disease severity and can lead to severe bleeding manifestations. This study aims to find the association of thrombocytopenia with other hematologic parameters.Materials and methods: This retrospective study enrolled 651 dengue patients tested at Patan Academy of Health Sciences who also underwent complete blood count at presentation.Results: Dengue-infected patients of all age groups with a slight male predominance. Thrombocytopenia was noted in 48.69% of cases. Thrombocytopenia showed a significant association with age (p=0.009), total leukocyte count(p=0.00), and hemoglobin levels (p= 0.015).Conclusions: Thrombocytopenia in dengue patients is frequently encountered. Increasing age, leukopenia, and anemia are factors significantly associated with thrombocytopenia at presentation.